Vai trò của kỳ vọng kết quả và cảm hứng với ý định khởi sự kinh doanh xã hội - Bùi Ngọc Tuấn, Anh; Phạm Xuân, Lan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study aims to determine the impacting mechanism of outcome expectations, inspiration on the social entrepreneurship intention through three components of the Theory of Planned Behavior (TPB) including attitude, subjective norm, and perceived behavioral control. These relationships are confirmed with 178 students who participated in programs or events organized by the social enterprise communities. Results PLS-SEM analysis shows the model fits well with research data also verify the significant influence of outcome expectations as well as inspiration in forming the social entrepreneurship intention. The results also validate the explanatory power of the TPB theory in the context of social entrepreneurship. The results were surprising as they showed that attitude, not perceived behavioral control, was the significant influence on the social entrepreneurship intention while subjective norm showed a slight effect. These findings help educators and policy-makers with the necessary suggestions to promote students' intention to start social entrepreneurship.
Keywords: Outcome expectations; Inspiration; Social entrepreneurship; Intention; TPB